Evidence for Specific Receptor‐Mediated Toxicity of Pharmaceuticals in Aquatic Organisms Derived from Acute and Chronic Standard Endpoints. (6th May 2021) - Coors, Anja; Falkenhain, Anna‐Maria; Scheurer, Marco; Länge, Reinhard
Abstract: The toxicity of 17 active pharmaceutical ingredients (APIs) was investigated using standardized acute and chronic tests with Daphnia magna and 2 algae species. Chronic toxicity was generally greater for Daphnia than for algae. Compilation of additional data resulted in 100 APIs for which the acute‐to‐chronic ratio (ACR) was determined for Daphnia . The frequency of high ACRs ( 20% with ACRs > 100) indicates that specific receptor‐mediated toxicity toward D. magna is rather common among APIs. The 11 APIs with ACRs > 1000 included lipid‐modifying agents, immunosuppressants, antibiotics, antineoplastics, antiobesics, antivirals, and antihistamines. There was no consistent association between ACR and chronic toxicity, ionization status, or lipophilicity. High ACRs were not exclusively associated with the presence of orthologs of the pharmacological target in Daphnia . Statins, acetylcholinesterase inhibitors, and antihistamines are discussed in more detail regarding the link between targets and toxic mode of action. For acetylcholinesterase inhibitors, receptor‐mediated toxicity was already apparent after acute exposure, whereas the high ACR and chronic toxicity of some antihistamines probably related to interaction with a secondary rather than the primary pharmacological target. Acute or modeled chronic toxicity estimates have often been used for prioritizing pharmaceuticals. This may be seriously misleading because chronic effects are currently not predictable for APIs with specific receptor‐mediated toxicity. However, it is exactly these APIs that are the most relevant in terms of environmental risks. Environ Toxicol Chem 2022;41:601–613. © 2021 SETAC